Where culture and mind meet : principles for a dynamic cultural psychology - Wagoner, Brady, 1980-; Carriere, Kevin R. (U.S.A : Information Age Publishing, 2021)
"Cultural psychology explores the mutual constitution of persons-minds and social-cultural worlds. It aims to be both transdisciplinary and international in its approach, and to develop theoretical models that remain faithful to people's lived experiences. This volume further advances these objectives through an exploration of core concepts (especially, normativity, liminality, and resistance), cultural psychology's foundations in philosophy, and the translation of theory into a methodology for investigating distinctly human ways of relating to the world"--
Includes bibliographical references.
Keywords: Ethnopsychology; Culture -- Psychological aspects; Social psychology